2000
DOI: 10.1046/j.1365-2044.2000.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Ease of tracheal intubation through the intubating laryngeal mask during manual in‐line head and neck stabilisation

Abstract: SummaryWe have studied core temperature changes occurring during induction of general anaesthesia and surgery in 18 patients undergoing elective aortic aneurysm repair. In the operating theatre, all patients were warmed with a forced-air warmer and a warming mattress, and received warmed (37 ЊC) intravenous fluids. Despite this, mean (SD) [range] core temperatures in the anaesthetic room decreased by 1.5 (0.3)[1.1-2.2] ЊC, while intravascular lines, epidural and urinary catheters were inserted before the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…The success rate of fibreoptic tracheal intubation through the intubating laryngeal mask at the first attempt (37 of 42 patients (88%)) in our study was similar to that in previous studies using the intubating laryngeal mask 7,8 and using the conventional laryngeal mask (90% to 95%). 1,13 Previous studies have reported that, when tracheal intubation was attempted blindly through the intubating laryngeal mask the success rate was high (93-100%).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The success rate of fibreoptic tracheal intubation through the intubating laryngeal mask at the first attempt (37 of 42 patients (88%)) in our study was similar to that in previous studies using the intubating laryngeal mask 7,8 and using the conventional laryngeal mask (90% to 95%). 1,13 Previous studies have reported that, when tracheal intubation was attempted blindly through the intubating laryngeal mask the success rate was high (93-100%).…”
Section: Discussionsupporting
confidence: 89%
“…1,13 Previous studies have reported that, when tracheal intubation was attempted blindly through the intubating laryngeal mask the success rate was high (93-100%). 8,9,14 However, this blind intubation may fail in 50-60% of patients at the first attempt 8,9,14 and might damage the larynx and surrounding tissues, such as impingement of the epiglottis into the laryngeal inlet 15 or perforation of a esophageal pouch. 16 Therefore, caution is required for the blind technique, 17 particularly when there is resistance during the advancement of a tracheal tube or when ventilation via the mask is suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 Nileshwar et al found only a non-significant trend toward higher overall intubation success with the Bullard laryngoscope when they compared its use vs blind intubation with the FT-LMA in a simulated setting of an unstable c-spine in 62 patients undergoing general anesthesia with the placement of manual in-line stabilization. 79 Asai et al 80 compared the ease of intubation (measured by a 100 mm VAS) by DL with a gum elastic bougie vs intubation via the FT-LMA using a FOB during manual in-line stabilization of 40 ASA I and II patients with no known upper airway pathology undergoing general anesthesia with muscle relaxant use. The success rate of intubation in the FT-LMA/FOB group was significantly higher than in the DL/bougie group (17/20 vs 9/20, respectively; P \ 0.01).…”
Section: Ventilationmentioning
confidence: 99%
“…Sample size was selected to detect a projected difference of 20% between groups for a type I error of 0.05 and a power of 0.8 with respect to intubation success rate in Cormack-Lehane grade 3/4 patients (based on a 60% incidence of grade 3/4 with manualin-line stabilization). 7 Descriptive data were tested using a two-tailed independent t test. Categorical data were tested by Chi-square test.…”
Section: Objectif : Comparer Le Stylet Fibroscopique (Sfs) Styletscopmentioning
confidence: 99%